1997
DOI: 10.1016/s0022-5223(97)70082-5
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-mediated gene transfer to lung isografts

Abstract: In vivo and ex vivo liposome-mediated gene transfer to lung isografts allows significant transgene expression with minimal effects on graft function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Our work proceeded from basic experiments of gene transfer in rat lung transplantation using adenoviral vectors at the time of organ harvest [16]. Transfer of the gene encoding for chloramphenicol acetyltransferase (CAT) resulted in expression up to 20 days following syngenic transplantation in inbred rats [17]. In subsequent experiments performed by Boasquevisque et al it has been demonstrated that liposome-mediated gene transfer of TGFP at the time of harvest reduces rejec-tion in allogenic rat lung transplantation [MI.…”
Section: Discussionmentioning
confidence: 99%
“…Our work proceeded from basic experiments of gene transfer in rat lung transplantation using adenoviral vectors at the time of organ harvest [16]. Transfer of the gene encoding for chloramphenicol acetyltransferase (CAT) resulted in expression up to 20 days following syngenic transplantation in inbred rats [17]. In subsequent experiments performed by Boasquevisque et al it has been demonstrated that liposome-mediated gene transfer of TGFP at the time of harvest reduces rejec-tion in allogenic rat lung transplantation [MI.…”
Section: Discussionmentioning
confidence: 99%
“…It was supplied by Genzyme Corporation, Framingham, Massachusetts, 12 and prepared as previously described. 1 Rat lung transplantation. An orthotopic left lung rat transplant model (Brown Norway donors to Fischer/F344 recipients) was performed by a modification of the "cuff technique" as described in detail elsewhere.…”
Section: Experimental Groupsmentioning
confidence: 99%
“…First, we had used this same route of delivery in previously published experiments in which we used reporter genes in rat lung grafts. 1,2 Second, it was technically easier to introduce a catheter into the left pulmonary vein rather than the left pulmonary artery. After storage for 3 hours in normal saline solution at 4°C, allografts were implanted.…”
Section: Experimental Groupsmentioning
confidence: 99%
“…W e have recently studied the feasibility, safety, and pattern of liposome-mediated gene transfer in a rat lung transplant model. 1,2 We demonstrated that gene transfer to rat lungs can be achieved with minimal toxicity when grafts are transfected either before retrieval (in vivo) or after organs had been harvested (ex vivo). We also showed that gene therapy techniques can bring functional benefits to lung grafts.…”
mentioning
confidence: 99%